IMPROVING STUDENTS’ PROBLEM SOLVING SKILL IN MATHEMATICS THROUGH WRITING - Linda Vitoria; Monawati Monawati (SCAD Independent, 2016)
This article describes the implementation of writing in Mathematics as an effort to improve students’ problem solving skill. The research method was classroom action research which was conducted in three cycles. Research participants were 24 first-year students at PGSD FKIP Syiah Kuala University. Data was collected using a written test consisted of mathematical word problems presented to the students at the end of each cycle, and interview. Students’ problem solving skill was analyzed based on the four steps of problem solving proposed by Polya: 1. the ability to understand the problem, 2. the ability to plan a strategy to solve the problem, 3. the ability to execute the plan, and 4. the ability to re-check. Result shows that writing in Mathematics improve students’ problem solving skill. In cycle 1, the average score of students’ problem solving skill was 51.7. In cycle 2, the average score was 75.6, and finally in cycle 3, the average score was 83.4. During interview, the students confessed that writing helped them organize their thinking so that they can solve a problem satisfactorily.